2021
DOI: 10.1186/s13063-021-05430-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of intramuscular administration of allogeneic adipose tissue derived and expanded mesenchymal stromal cells in diabetic patients with critical limb ischemia with no possibility of revascularization: study protocol for a randomized controlled double-blind phase II clinical trial (The NOMA Trial)

Abstract: Background Chronic lower limb ischemia develops earlier and more frequently in patients with type 2 diabetes mellitus. Diabetes remains the main cause of lower-extremity non-traumatic amputations. Current medical treatment, based on antiplatelet therapy and statins, has demonstrated deficient improvement of the disease. In recent years, research has shown that it is possible to improve tissue perfusion through therapeutic angiogenesis. Both in animal models and humans, it has been shown that ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…These attributes, together with their immunomodulatory properties and their regenerative capacity, make them excellent potential candidates for the treatment of hindlimb ischemia. MSCs have been tested in several preclinical studies ( Iwase et al, 2005 ; Al-Khaldi et al, 2003 ; Kinnaird et al, 2004 ), and although the majority of the reported clinical trials used autologous MNC, there are also some studies where MSCs have been and are currently being assessed for this purpose in patients, either delivered locally through the intramuscular route or systemically, with promising results ( Soria-Juan et al, 2019 ; Soria-Juan et al, 2021 ; Gupta et al, 2013 ). MSC effects may depend more on secreted soluble factors than on engraftment and transdifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…These attributes, together with their immunomodulatory properties and their regenerative capacity, make them excellent potential candidates for the treatment of hindlimb ischemia. MSCs have been tested in several preclinical studies ( Iwase et al, 2005 ; Al-Khaldi et al, 2003 ; Kinnaird et al, 2004 ), and although the majority of the reported clinical trials used autologous MNC, there are also some studies where MSCs have been and are currently being assessed for this purpose in patients, either delivered locally through the intramuscular route or systemically, with promising results ( Soria-Juan et al, 2019 ; Soria-Juan et al, 2021 ; Gupta et al, 2013 ). MSC effects may depend more on secreted soluble factors than on engraftment and transdifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized, placebo-controlled, multi-center study with single-dose intramuscular administration of ASCs from healthy donors in diabetic N-O CLI patients is ongoing [ 40 ].…”
Section: Adipose-derived Stem Cellsmentioning
confidence: 99%
“…Classification methods for CLI severity were devised to estimate amputation probability and treatment outcomes. Historically, the Fontaine and Rutherford classification systems categorized patients based on clinical criteria alone or in conjunction with objective hemodynamic evidence [ 72 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Benoit et al accomplished a meta-analysis that exhibited increased ABI values in 63.2% of patients, significantly increased TcPO2 in 76.9% of patients, pain relief in nearly 90%, and claudication interval extension in 89.5% of patients [ 3 ]. Angiography is a kind of functional endpoint that utilizes mean percentage vascular flow change from angiographic techniques, including duplex ultrasonography (DUS), computed tomography angiography (CTA), and magnetic resonance angiography (MRA), to evaluate the target limb's vascularity [ 72 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation